Application of Reproduction Biotechnology and Molecular Genetic to Improve Productivity of Local Pigs - Bayu Dewantoro Putro Soewandi (Indonesian Center for Animal Research and Development, 2017)
Low productivity in local pigs is due to the absence of breeding plan with mating arrangements. The main productivity variables used in breeding are litter size (number of piglets), weaning litter, number of teats, sow productivity index, growth rate, slaughter weight, and carcass quality. Selection to produce a new breed in breeding scheme should be conducted within five generations requiring large numbers of livestock, length period, and costly. Biotechnology reproduction and genetic molecular can be used to increase the value of the variables, to shorten interval generation, and cost efficient. This paper provides information on the use of reproduction biotechnology and molecular genetic from various sources and utilization of both technologies to increase local pig productivity. Reproductive biotechnology is useful in mating arrangement and molecular genetic using marker assisted selection (MAS) is able to determine superior pig since early age.